1997
DOI: 10.1086/516067
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features ofHelicobacter pyloriInfection in Developing Countries

Abstract: Helicobacter pylori infection has a worldwide distribution, and it has distinct epidemiological features in developing countries. In contrast to that in developed countries, H. pylori infection in developing countries seems to be nearly universal, beginning in early childhood. Children become infected in the first few months of life; in some communities as many as 50% of the children are infected by the age of 5 years, and up to 90% are infected by the time they reach adulthood. In some developing countries wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
153
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 9 publications
11
153
1
3
Order By: Relevance
“…By the age of five, as many as 50% are already infected, and by the age of 40, 90% are infected. 40 Prevalence rates are lower in developing countries with better industrialization, public health, and living conditions. Nevertheless, the rate is still several times higher than that found in developed countries, where the incidence of H. pylori infection is found in approximately 30% of the adult population.…”
Section: Epidemiological Features Of the Infectionmentioning
confidence: 99%
“…By the age of five, as many as 50% are already infected, and by the age of 40, 90% are infected. 40 Prevalence rates are lower in developing countries with better industrialization, public health, and living conditions. Nevertheless, the rate is still several times higher than that found in developed countries, where the incidence of H. pylori infection is found in approximately 30% of the adult population.…”
Section: Epidemiological Features Of the Infectionmentioning
confidence: 99%
“…For example, there are differences in H. pylori susceptibility between African Americans and US residents of European ancestry after adjusting for socioeconomic status, age and living conditions (Graham et al, 1991). Approximately 5% to 10% of a population is never infected with H. pylori, even in the presence of high exposure rates (Bardhan, 1997). Twin study has showed that there is significantly higher concordance for H. pylori infection in monozygotic compared with dizygotic twins, with a heritability estimate in twins of 57% (Malaty et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…58 In developing countries, prevalence approaches 90%, with most individuals infected before age 10 years. 59,60 Environmental factors other than H. pylori also influence the risk of developing gastric cancer. Consumption of fresh fruits and vegetables has been associated consistently with lowered risk of the disease.…”
Section: Discussionmentioning
confidence: 99%